Construction of SiO2@UiO-66 core–shell microarchitectures through covalent linkage as flame retardant and smoke suppressant for epoxy resins. (1st November 2019) - Guo, Wenwen; Nie, Shibin; Kalali, Ehsan Naderi; Wang, Xin; Wang, Wei; Cai, Wei; Song, Lei; Hu, Yuan
Abstract: The SiO2 @metal organic framework (Universitetet i Oslo-66, UiO-66) core–shell microspheres were constructed through covalent linkage between amine groups in UiO-66-NH2 and epoxy groups on the surface of silica. The morphology and size of the SiO2 @UiO-66 core–shell microspheres could be simply controlled by tuning the ratio between UiO-66-NH2 and epoxy terminated silica (E-SiO2 ). As observed by TEM, the SiO2 @UiO-66 hybrids showed better dispersion state within epoxy matrix compared to either E-SiO2 or UiO-66-NH2 . The incorporation of SiO2 @UiO-66 hybrids slightly promoted the thermal degradation of the resultant epoxy composites but improved residual yield. The dynamic mechanical analysis results indicated that the SiO2 @UiO-66 hybrids slightly increased the glass transition temperature and the modulus. The SiO2 @UiO-66 hybrids exhibited higher efficiency in reducing the heat release rate and the smoke production rate compared to either E-SiO2 or UiO-66-NH2 . The influence of the component ratio in SiO2 @UiO-66 on flame retardancy of the epoxy composites was also studied by cone calorimeter. Specifically, the SiO2 @UiO-66 hybrid with medium ratio (SiO2 @UiO-66-2) exhibited maximum reduction in peak heat release rate (−31%), total heat release (−23%) and total smoke production (−16%). The char residues were investigated by the Fourier transform infrared spectra, scanning electron microscopy and X-ray photoelectron spectroscopy, which demonstrated that the enhanced flame retardancy of EP/SiO2 @UiO-66-2 was attributable to the continual morphology and high thermal resistance originated from the presence of the silicon and zirconium complex. These favorable characteristics including high flame retardant efficiency and good smoke suppression make SiO2 @UiO-66 hybrids promising for flame retardant polymers application. Highlights: The SiO2 @UiO-66 hybrids showed core–shell microsphere structure . The addition of 3 wt% SiO2 @UiO-66-2 caused 31% reduction in peak heat release rate. The addition of 3 wt% SiO2 @UiO-66-2 led to 16% reduction in total smoke production.